An essential model for leaders to enable integrated working to flourish: a qualitative study examining leaders of Children's Centers. - Vaggers, J.; Anderson, E.S (Journal of Interprofessional Care)
Today's era of integrated working seeks to bring together different professionals to work in patient-centered teams. As a result leadership perspectives have changed. We now seek leaders who recognize the complexity of moderating across different health, social care and other public and private sector organizations for collective patient/community focussed service. This research focuses on the role of leaders in the UK who were asked to lead a range of practitioners working from Children's Centers. These centers brought together a myriad of practitioners from health, social care, and education to meet the needs of children from wide and diverse backgrounds. We share a qualitative study, exploring the experiences of Children's Center leaders, using critical theory and constructivism. The study explored how leaders enable integrated working to flourish. The research was conducted in two stages: In Stage One, five strategic Children's Center managers were interviewed to illuminate the key ingredients felt to support good leaders. Stage Two brought together 10 Children's Center leaders from across different areas of the UK, to share their experiences using Participatory Action Research. The final synthesis identified four main processes which could help leaders to enable integrated working to flourish. These were: i) Thinking Systematically; ii) Building and re-building relationships; ii) Nourishing self-actualization and; iv) Utilizing alternative approaches to problem solving. Four borderline processes were identified: Interaction, Integrity, Flow and Sensitivity. The final model articulates the skills required to lead integrated services which bring together a wide range of practitioners. The outcomes help leaders to explore new ways of leading and require further testing. The outcomes may apply to other clinical areas of integrated working.